PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI PADA KELUARGA MUDA DI RA MIFTAHUL HUDA KRAMATAGUNG BANTARAN PROBOLINGGO TAHUN PELAJARAN 2019-2020 - Terza Travelancya DP. (Al-Fikru : Jurnal Pendidikan Dan Sains, 2020)
This study aims to describe the social emotional development of early childhood in young parents in Raudhatul Athfal Miftahul Huda Kramatagung Bantaran, Probolinggo. Descriptions related to the socialization process and students' emotions in school. This research is a qualitative descriptive research with the subject of young parents in RA Miftahul Huda, Kramatagung Village, Bantaran District, Probolinggo Regency, as well as with the object of early childhood social emotional development. The data processing stages carried out include: 1) Data reduction, setting aside irrelevant data and drawing conclusions; 2) Display data, present and describe data in a narrative form; 3) Verification and confirmation of conclusions, drawing conclusions obtained from the data collection process using observation and interview techniques. The triangulation used is source triangulation and method triangulation. The results showed that the social development of early childhood in young families was as follows: 1) The method used by parents in educating early childhood was giving punishment, not accompanying children directly, giving orders to children, 2) social development of older children in the family. young people tend not to have an independent attitude. 3) The emotional development of early childhood in young families tends to be negative. Key words: social development, emotional development, young family